Pengaruh Kreativitas Guru Pendidikan Agama Kristen terhadap Minat Belajar Siswa di SD Kasih Anugrah, Jakarta Barat - Zebua, Deshilda Sandika (Sekolah Tinggi Teologi Hagiasmos Mission, 2020)
Student interest in learning is one of the critical success factors of learning. Because if there is no motivation within students to learn, of course learning success will be difficult to create even though educators have sought co-ops. The teacher must be able to be an inspiration for students so students will be more motivated by their interest in learning. Teacher creativity in learning can be a solution to solve problems regarding the lack of student interest in learning. This study aims to analyze the influence of PAK teacher creativity on student learning interest, especially in Christian religious education subjects at SD Kasih Anugrah Tegal Alur, West Jakarta. The method used in this research is a quantitative method and takes place at the Kasih Anugrah Elementary School in Tegal Alur, West Jakarta. The population in this study were grade V and IV students, amounting to 100 students. The first sample was 37 students, and the second sample was 50 students. Data collection techniques using interviews, questionnaires, and documentation. The data analysis technique used in this study is the Linear Regression formula. The results of this study indicate the value of Sig